(untitled) (Journal of Renal and Hepatic Disorders, 2021)
Self-insertion of a foreign body in the urethra is an uncommon presentation clinically. The cases usually arise due to fulfillment of sexual desire, for recreation, play, or exploration, or the foreign body insertion may take place accidentally. We present a case of an adolescent boy with a foreign body urethra presenting to the emergency room with urinary retention, pain, and dysuria. Attending urologist suspected urethral stricture and ordered ultrasonography to investigate which turned out to be a sewing needle in his urethra. The patient was then enquired about the foreign body. He tried to self-dilate his urethra as he was experiencing lower urinary tract symptoms. The sewing needle was removed by endoscopy and he was administered with antibiotics and painkillers. The urethral foreign bodies may present with pain, dysuria, or urinary incontinence and these foreign bodies are mostly seen in the male population in the adolescent age group.